Devarim Based on a Novel by Yaakov Shabtai - Shabatai, Ya'ackov (Amos Gitai - Volume 2, 2012)
First part of the trilogy on cities, after the novel by Yaakov Shabtai (Past Continuous). The film depicts the spiritual disarray of three men in their thirties and forties, in the agitation and turmoil of Tel Aviv, the city created by Jewish pioneers in 1909. None of them has the life he had imagined. [www.amosgitai.com]